Museums as Spaces for History Learning and Educational Tourism : Shaping Students’ Creativity and Understanding - Fiona Puspita Sari; Arif Saefudin (Tarikhuna: Journal of History and History Education, 2024)
Museums are often underutilised as learning resources, despite their great potential to enhance students' historical understanding and creativity. This lack of utilisation results in limited in-depth and enjoyable learning experiences for students. This research aims to identify the benefits of museums as a source of learning history and its role as an educational tourism destination. The method used is a qualitative method with data collection techniques through observation, interviews, and documentation. The results showed that museum visits as an outdoor learning model can improve students' understanding, create a more enjoyable learning atmosphere, and encourage student creativity. In addition, the museum also acts as an educational tourism destination that enriches people's insights about cultural heritage. The findings emphasise the importance of museum integration in the educational process and as a means of educational tourism, by providing practical recommendations for teachers and educational institutions to make optimal use of museums in learning activities.